Sosialisasi Budidaya Hidroponik Sebagai Upaya Peningkatan Pengetahuan Mahasiswa Tingkat I di Politeknik Pembangunan Medan - Ameilia Zuliyanti Siregar; Dani Febriansyah; Damayanty Damayanty; Al Insyirah; Aulia Manda Br Ginting; Akha Zilan Putra Asto; Addiena Kinanthi Alfiah; Gusti Setiavani; Dinda Puspita (PT. Intelek Cendikiawan Nusantara, 2025)
The socialization of hydroponics cultivation is strategic effort to improve students understanding of modern agriculture technology that is efficient, practical, and sustainable.